A Cytop Insulating Tunneling Layer for Efficient Perovskite Solar Cells. Issue 10 (15th September 2017) - Zheng, Yifan; Shi, Wei; Kong, Jaemin; Huang, Di; Katz, Howard E.; Yu, Junsheng; Taylor, André D.
Abstract: Improvement of the interface between the perovskite layer and the electron‐transport layer (ETL) is critical toward the advancement of planar perovskite solar cells (PSCs). It is important to obtain a uniform and pinhole‐free ETL that can minimize film defects and thus undesirable electron–hole recombination between the perovskite layer and cathode. However, this is extremely difficult because the rough perovskite surface causes charge–carrier recombination, facilitates large leakage currents, and inevitably deteriorates the electron‐extraction efficiency. Here, fluorine‐containing insulating polymers, poly(perfluorobutenylvinylether) (Cytop), are used as the tunneling layer in planar PSCs for the first time, resulting in a significant improvement in the power conversion efficiency (PCE) from 11.9% to over 14.5%. It is found that the Cytop layer not only fills the pinholes of the perovskite surface to decrease the trap concentration, but can also provide a strong electron‐extraction ability to facilitate charge‐transfer process and restrict charge recombination. In addition, improved water resistance is demonstrated using Cytop, which significantly extends the PSC lifetime (78% of initial PCE vs 22% for control after 1500 h) and increases the practical applicability. Abstract : Fluorine‐containing insulating polymers, poly(perfluorobutenylvinylether) (Cytop), are used as the tunneling layer in a planar perovskite solar cell for the first time. Overall, by fully understanding the mechanism of the Cytop insulating tunneling layer, a significant improvement in the power conversion efficiency is obtained from 11.9% to over 14.5%, with long device lifetime and high potential for practical applications.